Adiponectin and resistin in acutely ill and weight-recovered adolescent anorexia nervosa: Association with psychiatric symptoms. (21st October 2019) - Tyszkiewicz-Nwafor, Marta; Slopien, Agnieszka; Dmitrzak-Węglarz, Monika; Rybakowski, Filip
Abstract: Objectives: Anorexia nervosa (AN) is a chronic illness where restriction of food intake results in decreased adipose tissue. The aim of this study was to measure the concentration of adiponectin and resistin in acute and partially weight-recovered anorectic inpatients. The associations of their levels with eating disorder symptoms were also assessed. Methods: A longitudinal study was conducted on 76 adolescent patients (ANG) and 30 age-matched healthy girls (CG). Selected adipokines serum levels, as well as the severity of depressive, obsessive-compulsive and disturbed eating behaviours, were analysed in the group of anorectic patients before (accAN) and after weight gain (recAN) and compared with the CG. Results: The concentration of adiponectin in the accAN was higher than in the CG ( P  = 0.05) and increased in recAN ( P  = 0.01). Resistin concentrations were lower in accAN and recAN than in the CG ( P =  0.00). A negative correlation between adiponectin and the scores in Yale-Brown Obsessive Compulsive Scale as well as positive between resistin and Beck Depression Inventory were found. Conclusions: In the acute AN, adiponectin and resistin levels are impaired and partial weight recovery fails to normalise them thus we suggest that they can be involved in the chronicity of certain symptoms. The level of adiponectin is associated with obsessive and compulsive symptoms and resistin with depressive symptoms, which indicates their potential contribution to the regulation of emotions and behaviours in AN.